Effects of Dietary Protein Source and Feeding Regime on Growth Performance, Nutrient Digestibility, Fatty Acids, and Quality Characteristics of Rainbow Trout, Oncorhynchus mykiss, Fillets. Issue 4 (29th April 2016) - Gai, Francesco; Peiretti, Pier Giorgio; Brugiapaglia, Alberto; Gasco, Laura
Abstract: This study investigated the effects of dietary protein source and feeding regime (apparent satiation and rationed) on growth performance, nutrient digestibility, fatty acid (FA) profile, and fillet quality traits in rainbow trout. A stock of 1200 juvenile trout (mean weight 114.6 ± 0.2 g) were randomly distributed into 24 fiberglass tanks (four diets × three replications × two feeding regimes). The experimental diets were formulated to be isoproteic and isoenergetic based on bacterial protein meal (BPM), pea protein concentrate (PPC), mixture thereof (MIX), and fish meal (FM), respectively. The feeding trial lasted 77 d with water temperature of 13 C. Statistical differences appeared among the diets only in terms of crude protein digestibility. Growth performance and somatic indexes were significantly affected by the diet, while only the condition factor was influenced by the feeding regime. None of the parameters appeared to be affected by the interaction effects. Differences appeared between the FA profiles of the dorsal muscle. Oleic, linoleic, α‐linolenic, and docosahexaenoic acid contents were influenced by diet, while only minor FAs were influenced by feeding regime. In conclusion, growth performance and nutrient digestibility resulted lower in fish fed BPM diet than other groups, while PPC group was similar to FM group.